2021
DOI: 10.3390/molecules26010189
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation in Local Infection

Abstract: Iron is an essential element in multiple biochemical pathways in humans and pathogens. As part of the innate immune response in local infection, iron availability is restricted locally in order to reduce overproduction of reactive oxygen species by the host and to attenuate bacterial growth. This physiological regulation represents the rationale for the therapeutic use of iron chelators to support induced iron deprivation and to treat infections. In this review paper we discuss the importance of iron regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 90 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…Deferrioxamine, a drug that has shown the ability to disrupt biofilms integrity ( Ishida et al, 2011 ), was found to have proprieties similar to IP6, where both have significant iron-chelating properties ( Hawkins et al, 1993 ). Studies have shown that iron-chelating agents are effective against pathogenic organisms ( Coraça-Huber et al, 2018 ; Scott et al, 2021 ), presumably because iron is an important component for bacterial proliferation and biofilm formation ( Lin et al, 2012 ; Farrand et al, 2015 ). Hence, it is plausible to speculate that iron-chelation by IP6 might play a role in its broad-spectrum antibacterial and antibiofilm activity reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Deferrioxamine, a drug that has shown the ability to disrupt biofilms integrity ( Ishida et al, 2011 ), was found to have proprieties similar to IP6, where both have significant iron-chelating properties ( Hawkins et al, 1993 ). Studies have shown that iron-chelating agents are effective against pathogenic organisms ( Coraça-Huber et al, 2018 ; Scott et al, 2021 ), presumably because iron is an important component for bacterial proliferation and biofilm formation ( Lin et al, 2012 ; Farrand et al, 2015 ). Hence, it is plausible to speculate that iron-chelation by IP6 might play a role in its broad-spectrum antibacterial and antibiofilm activity reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Iron chelators have higher affinity constants for iron and therefore, prevent the accumulation of excess iron and challenge the fungal growth with the iron-depleting environment (Symeonidis 2009 ). Food and drug administration (FDA) approved iron chelators include oral tablets such as Deferiprone (DFP), Deferasirox (DFX), and injectable Desferrioxamine (DFO) (Scott et al 2021 ). DFO received FDA approval for treating iron overload in transfusion-dependent anemia in the year 2005.…”
Section: Management Of Mucormycosismentioning
confidence: 99%
“…This suggests that preventing metal acquisition by fungal pathogens through metal chelation is an alternative approach to copy with fungal infections. Iron is the most abundant trace metal and an essential nutrient for eukaryotic cells ( 7 , 8 ). Because of its redox properties, it plays a pivotal role in many core metabolic pathways, such as cell respiration, electron transport chains, iron-sulfur cluster assembly, and oxygen transfer ( 9 ).…”
Section: Introductionmentioning
confidence: 99%